Effect of Mycorrhiza and Vermicompost on Drought Tolerance of Lime Seedlings (Citrus aurantifolia Cv. Mexican Lime). Issue 3 (2nd July 2020) - Zeighami Nejad, Kobra; Ghasemi, Mostafa; Shamili, Mansoore; Damizadeh, Gholam Reza
ABSTRACT: In order to investigate the effect of mycorrhizal arbuscular fungi (MAF) and vermicompost on drought tolerance of Mexican Lime seedlings ( Citrus aurantifolia cv. Mexican Lime), a factorial experiment was conducted as a completely randomized design in greenhouse conditions. Factors included were water stress at three levels (100% ETc, 70% ETc and 40% ETc ) and biofertilizers at three levels (0, 100 g mycorrhiza, 100 g vermicompost per pot) with four replications. Irrigation treatments were applied for two months on one year seedlings. The results showed that growth of leaf and root was significantly affected by drought stress and decreased, whereas the effect of drought stress on fresh and dry weight of stem was not statistically significant. According to the results, the rate of decrease in fresh and dry weight of leaves under severe water stress treatment compared to full irrigation was 35.38 and 31.79%, respectively. Also, the rate of decrease in fresh and dry weight of root in severe water stress treatments was 35.53 and 34.11%, respectively, compared to full irrigation. Inoculation of seedlings with bio-fertilizers especially 100 g mycorrhiza per pot significantly increased leaf fresh weight (19.94%), leaf dry weight (17.31%), stem fresh weight (26.7%), stem dry weight (26. 1%), root fresh weight (35.53%), root dry weight (14.82%), RWC (76.19%), enzyme activity, chlorophyll a (0.637 mg.g f.w.), b (0.372 mg.g f.w.) and carotenoid (11 mg.g f.w.) and reduced ion leakage (62.5%) compared to non-inoculated seedlings. Based on the results, it can be stated that application of 100 g bio-fertilizer could reduce adverse effects of drought stress on the Mexican Lime seedlings.